Cannabis Extraction Technologies: Impact of Research and Value Addition in Latin America - Suárez-Jacobo, Ángela; Díaz Pacheco, Adrián; Bonales-Alatorre, Edgar; Castillo-Herrera, Gustavo Adolfo; García-Fajardo, Jorge Alberto (Molecules (Basel, Switzerland), 2023)
The Cannabis genus of plants has been widely used in different cultures for various purposes. It is separated into three main species: sativa, indica, and ruderalis. In ancient practices, the plant was used as a multipurpose crop and valued for its fiber, food, and medicinal uses. Since methodologies for the extraction, processing, and identification of components have become available, medical, and food applications have been increasing, allowing potential development in the pharmaceutical and healthy functional food industries. Although the growing legalization and adoption of cannabis for the treatment of diseases are key factors pushing the growth of its market, the biggest challenge is to obtain higher-quality products in a time- and cost-effective fashion, making the process of extraction and separation an essential step. Latin American countries exhibit great knowledge of extraction technologies; nevertheless, it is still necessary to verify whether production costs are economically profitable. In addition, there has been an increase in commercial cannabis products that may or may not be allowed, with or without quality fact sheets, which can pose health risks. Hence, legalization is mandatory and urgent for the rest of Latin American countries. In this article, the phytochemical compounds (cannabinoids, terpenes, and phenolic compounds), the current status of legalization, extraction techniques, and research advances in cannabis in Latin America are reviewed.